Maintenance management and servises (case study: PERKESO building's in penisular of Malaysia) - Hashim, Ahmad Riza (2006)
Maintenance Management and Services is a combination of several actions in which to retain or restore an item to perform its required action. PERTUBUHAN KESELAMATAN SOSIAL (PERKESO) as one of the semi government sector in Malaysia that has many assets, needs maintenance to prevent the assets from deterioration. Maintenance in PERKESO was monitor and control by Property Unit and Local PERKESO Office. There are two maintenance system presently implemented at PERKESO: Preventive maintenance and Corrective Maintenance. The maintenance and services in PERKESO are divided to two building type: stand alone building and shop lot building. Maintenance and services for stand alone PERKESO building is total preventive maintenance and services scope and for shop lot PERKESO building scope maintenance and services only cover cleaning, M&E preventive maintenance and Pest Control. Aim of this study to propose maintenance management & services system. To achieve the aim of this study, five objectives have been set, to study the maintenance management system presently implemented. To identify the common problem in maintenance management and services. To identify the tenant satisfactory level upon the maintenance and services implemented. To identify tenant opinion to make improvement for maintenance management and services. From the data analyze and propose maintenance management and services system. This research focused on PERKESO Building’s in Peninsular of Malaysia. To obtain the data the following knowledge acquisition methods were used by interview, questionnaire and archives. An interview were set for two session, pre-interview done before set questionnaire and interview after the analysis data had done Result of the study showed the responds of the end user customer for the overall building conditions and the services given is fair. To achieve the tenants’ satisfaction level, a new maintenance management system is proposed.